Insurgent encounters transnational activism, ethnography, and the political - Juris, Jeffrey S. 1971-; Khasnabish, Alex 1976- (Duke University Press, 2013)
Ethnography and activism within networked spaces of transnational encounter / Jeffrey S. Juris and Alex Khasnabish -- Spaces of intentionality: race, class, and horizontality at the United States social forum / Jeffrey S. Juris -- Tracing the Zapatista rhizome, or, the ethnography of a transnationalized political imagination / Alex Khasnabish -- The possibilities and perils for scholar-activists and activist-scholars: reflections on the "feminist dialogues" / Manisha Desai -- From local ethnographies to global movement: experience, subjectivity, and power among four alter-globalization actors / Geoffrey Pleyers -- The global indigenous movement and "paradigm wars": international activism, network building, and transformative politics / Sylvia Escárcega -- Local and not-so-local exchanges: alternative economies, ethnography, and social science / David J. Hess -- The edge effects of alter-globalization protests: an ethnographic approach to summit-hopping in the post-Seattle period / Vinci Daro -- Transformations in engaged ethnography: knowledge, networks, and social movements / Maria Isabel Casas-Cortés, Michal Osterweil, and Dana E. Powell -- Transformative ethnography and the world social forum: theories and practices of transformation / Giuseppe Caruso -- Activist ethnography and translocal solidarity / Paul Routledge -- Ethnographic approaches to the world social forum / Janet Conway -- The transnational struggle for information freedom / M. K. Sterpka -- This is what democracy looked like / Tish Stringer -- The cultural politics of free software and technology within the social forum process / Jeffrey S. Juris, Giuseppe Caruso, St¿phane Couture, and Lorenzo Mosca -- The possibilities, limits, and relevance of engaged ethnography / Jeffrey S. Juris and Alex Khasnabish